Computational Processing for Concept Network Analysis in Educational Programs - A Comparative Study between Arabic and Foreign Programs - بوخالفة نهى ياسمين – العلمي سعدية (university of eloued جامعة الوادي, 2024)
الملخص: أكدت المعالجة المحوسبة للغة والنص (NLP) قدرة هذا النهج في تحليل النصوص واستخلاص المصطلحات والمفاهيم الأساسية لفهم الرسالة المعرفية للنص. تهدف الدراسة إلى تحديد أهم المصطلحات والعلاقات الدلالية بينها في البرامج التربوية العربية والأوروبية، واستخدام تقنية تحليل شبكة النص لتحديد مستوى حضور هذه المصطلحات وطبيعة العلاقات بينها، بهدف استخلاص الرسالة المعرفية المستهدفة من هذه البرامج. في هذه الدراسة سنطرح الإشكاليات التالية ضمن مجال المعالجة الآلية للغات الطبيعية : ماهي أهم المصطلحات التي تستوطن البرامج التربوية العربية والأوروبية؟ وماهي طبيعة العلاقات الدلالية بينها ؟ وبالتالي ماهي أهم المفاهيم المودعة فيهم ؟ وماهي الرسالة المعرفية المستهدفة من هذه البرامج التربوية ؟ Résumé : فرنسية أو انجلزية Computerized language and text processing (NLP) has confirmed the ability of This approach to analyze texts and extract basic terms and concepts to Understand the cognitive message of the text. The study aims to identify the Most important terms and the semantic relationships between them in Arab and European educational programs, and to use the text network analysis technique To determine the level of presence of these terms and the nature of the Relationships between them, with the aim of extracting the targeted cognitive Message from these programs. In this study, we will raise the following Problems within the field of automatic processing of natural languages : What Are the most important terms that inhabit Arab and European educational Programs ? What is the nature of the semantic relationships between them ? Therefore, what are the most important concepts deposited in them ? What is The intended cognitive message of these educational programs ?
memoier master informatique
Keywords: عربيّــة: محوسبة، النص، برنامج تربوي، مصطلح، مفهوم، علاقة دلالية. فرنسيــة او إنجليزية: computerized text processing. Educational program term. The